Point-Prevalence Survey of Antimicrobial Use and Healthcare-Associated Infections in Four Acute Care Hospitals in Kazakhstan - Yuliya Semenova; Aizhan Yessmagambetova; Zaure Akhmetova; Manar Smagul; Akniyet Zharylkassynova; Bibigul Aubakirova; Kateryna Soiak; Zhanar Kosherova; Ainur Aimurziyeva; Larissa Makalkina; Ainur Ikhambayeva; Lisa Lim (MDPI AG, 2024)
Background/Objectives: Few studies have examined the prevalence of healthcare-associated infections (HAIs) and antimicrobial use (AMU) in acute care hospitals in Kazakhstan. This study aimed to address this gap by conducting a point-prevalence survey (PPS) of HAIs and AMU, as well as evaluating hospital antibiotic consumption via internationally recognized methodologies. Methods: PPS was conducted in four acute care hospitals in Kazakhstan on 11 May 2022, following the methodology of the European Center for Disease Prevention and Control, and included 701 patients. Antibiotic consumption in the same hospitals was assessed via the Global Antimicrobial Resistance and Use Surveillance System methodology. Results: HAIs were observed in 3.8% of patients (27/701), with intensive care unit wards accounting for 48.1% of these cases (13/27). Pseudomonas aeruginosa was the most frequently identified pathogen (5 out of 14 documented cases, 35.7%). Resistance to carbapenems was the most common resistance, followed by resistance to glycopeptides and third-generation cephalosporins. The rate of AMU was 38.2%, with an average of 1.37 antibiotics administered per patient. Surgical prophylaxis lasting more than one day was the most common indication for antimicrobial prescription (44.8%). Ceftriaxone and cefazolin are the most commonly used antibiotics. Conclusions: The results of this study are important for understanding the current situation in Kazakhstan and for informing national antimicrobial stewardship and infection control strategies.